Improving the Business Automation offer of a technology consulting company in Portugal - Luís Carlos Moreira Fernandes (2021)
The world of Business Automation has been developing gradually over the decades. Now, the drive for automation is both inevitable, and irreversible. Business Automation ultimate goal is to incorporate technology and agile methodology to build automated processes that will maximise business performance. The field seeks to enhance agility, increase efficiency, optimize employee productivity and upgrade customer experience. With technology mature enough to scale, Business Automation became a natural pillar of any digitisation journey. This research intends to explore the Business Automation domain, by understanding how it can lead Digital Transformation and identify opportunities to improve a Business Automation offer of a technology consulting company in Portugal. This study was carried out using a Double Diamond methodology, a well-known creative and flexible process, with a clear roadmap, and it incorporated both quantitative and qualitative data, with case studies analysis and semi-structured interviews. The author aimed at quantitative research to serve as the foundation for the qualitative approach, to accomplish credible solutions to respond to the research questions. Besides confirming the evolution Business Automation had taken so far, this study explored three improvements to the service concept of the Business Automation offer of a technology consulting company, allowing it to develop a more solid practice, both from a sales and an implementation perspective, focusing on strategic targeted customers.